Heredia, urban space and youth: transformations in urban space - Araya Ramírez, Iliana (Revista Geográfica de América Central., 2024)
This article aims to characterize the transformations of urban space and the impact of place appropriation by the youth of Heredia within the context of globalizing neoliberal capitalism. The methodological approach is qualitative, employing the method of spatial life narratives through the technique of life stories. Fieldwork was conducted between March 2015 and February 2017. The results are presented according to the urban typology comprising a) residential zone, b) commercial zone, c) university zone, and d) social exclusion zone. The work presented in this chapter is part of the results of the doctoral thesis titled “Spatial Representations: From Geographic Imagination to Lived Space.”